The Global Shipping Sector Amid COVID-19: Challenges and Adaptations to Global Maritime Transportation (2019-2022) - Majeed, Dr. Saima; Urooj, Shaista; Sher, Shaheer Umer; Asad, Muhammad; Ali, Ahsan; Idrees, Mohammad; Medson, Cecelia (Journal of Nautical Eye and Strategic Studies, 2024)
The emergence and spread of novel coronavirus (SARS-CoV-2) has significantly affected the entire world’s health and macroeconomic dynamics. Other dominating economic sectors including the global maritime industry, which comprises various areas of expertise, present international employment opportunities and have also undergone substantial stress. The consequences of the outbreak of coronavirus pandemic presented unprecedented challenges to global industries, with the shipping sector bearing a particularly heavy burden. This study comprehensively examines the ripple effects of SARS-CoV-2 on the shipping trade, considering factors for instance disrupted trade routes, labor shortages, and port closures. The research study also aims to contribute insights essential for building a more adaptive and resilient global shipping landscape in the wake of COVID-19 or similar pandemics. A combination of quantitative analysis, historical comparisons, industry insights, and case studies was used in the methodology to examine how COVID-19 would affect shipping volumes, container traffic, and port activities. These methods made it easier to comprehend the pandemic effects on the global shipping industry by incorporating real-world experiences. The results demonstrate that most respondents agree COVID-19 has prominently affected the shipping industry, leading to increased container costs and a greater focus on sustainability and environmental practices. Additionally, while many respondents believe the industry is prepared for future crises, a significant number are confident that shipping companies have adopted new health and safety protocols. The findings demonstrate that 30.6% of companies were significantly impacted by challenges in importing inputs from overseas. Export difficulties have led to decreased domestic sales, exacerbated by increased trade costs due to COVID-19 travel restrictions. In response to the challenges posed, the study proposed practical recommendations to minimize future risks, enhance supply chain resilience, and ensure the uninterrupted flow of global shipping operations.